How Do Rural Schools Fare Under a High-Stakes Testing Regime? - Frank D. Beck (Journal of Research in Rural Education, 2005)
Analyses of data from the Illinois Standards Achievement Test (ISAT) show how strongly associated the socioeconomic characteristics of schools are with school outcomes. Factors such as the percentage of students who are poor, percentage black, and the property values within a district explain over 70% of the variance in school outcomes. However, the state has created a high-stakes designation system, using yearly test scores as a snapshot of school performance. Schools would be sanctioned or rewarded more on levels of poverty and racial characteristics than on gain scores. We extend this research by linking county level data to the 2000 ISAT data for Illinois' public schools. We examine the extent to which rurality matters for school outcomes and the extent to which the Illinois' school designation system unfairly targets poor rural schools. We find that rural schools in Illinois perform better than their suburban or urban counterparts on the state's standardized test. Despite this, the high stakes test and designation system being considered by the state will unfairly benefit suburban schools.